2000
DOI: 10.1074/jbc.m002497200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Estrogen Receptor Ligand Binding Domain Discriminate between Hormone-dependent Transactivation and Transrepression

Abstract: The estrogen receptor (ER) suppresses transcriptional activity of the RelA subunit of nuclear factor-B in a hormone-dependent manner by a mechanism involving both the receptor DNA binding domain and ligand binding domain (LBD). In this study we examine the role of the ER LBD in mediating ligand-dependent RelA transrepression. Both ER␣ and ER␤ inhibit RelA in response to 17␤-estradiol but not in the presence of antihormones. We have identified residues within the ER␣ LBD that are responsible for receptor dimeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
53
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 72 publications
7
53
0
Order By: Relevance
“…Taken together, these results indicate that the ability of ERa to inhibit REL-directed transactivation is enhanced by estrogen. Similar to our results, estrogen has previously been shown to enhance the ability of ERa to repress RelA-dependent transactivation (Valentine et al, 2000).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Taken together, these results indicate that the ability of ERa to inhibit REL-directed transactivation is enhanced by estrogen. Similar to our results, estrogen has previously been shown to enhance the ability of ERa to repress RelA-dependent transactivation (Valentine et al, 2000).…”
supporting
confidence: 92%
“…Several previous reports have demonstrated that fulllength ERa can inhibit NF-kB-induced transactivation in an estrogen-dependent manner (Ray et al, 1994;Stein and Yang, 1995;Ray et al, 1997;Cerillo et al, 1998;Valentine et al, 2000;Evans et al, 2001;Sharma et al, 2001;Tzagarakis-Foster et al, 2002), but the mechanism by which this inhibition occurs is unclear. However, two studies have reported that ERa can bind preferentially to REL, as compared to other NF-kB subunits.…”
mentioning
confidence: 99%
“…The inhibition of NF-B transcriptional activity by E2 bound to ER␣ or ER␤ has been well documented (6,27). Here, we demonstrate that WAY-169916 retains the ability to inhibit NF-B activity through both human ER␣ and ER␤ in vitro with little or no induction of CK activity, suggesting that WAY-169916 pharmacologically dissociates the NF-B-suppressive activity of ER from its transcriptional activity.…”
Section: Discussionsupporting
confidence: 53%
“…The ability to dissociate these two activities has been previously demonstrated by using site-directed mutagenesis on ER␣. Mutations within both helix 12 and helix 3 of ER␣ were identified that impaired ER transcriptional activity but retained the ability to antagonize NF-B transcriptional activity in a ligand-dependent fashion (27). It will be important to determine whether these residues also contribute in the selectivity observed with WAY-169916.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation